When someone you love suffers from posttraumatic stress : what to expect and what you can do - Zayfert, Claudia; DeViva, Jason C. (New York : Guilford Press, 2011)
'Trauma survivors frequently struggle with unwanted memories, intense emotions, and problems with everyday functioning. Effective help is out there, but the needs of family members--confused and scared about what has happened to the person they love--are often overlooked. Will the person with posttraumatic stress ever get better? How can spouses and other loved ones promote healing? Where can family members turn when they feel like they just can't cope? From experienced trauma specialists Drs. Claudia Zayfert and Jason C. DeViva, this highly practical guide is packed with information, support, vivid stories, and specific advice. Readers learn to navigate the rough spots day by day and help their loved one find a brighter tomorrow'--
Machine generated contents note: Introduction I. Understanding Posttraumatic Stress 1. What It Feels Like to Live with a Trauma Survivor 2. How Trauma Affects Survivors 3. Why Is Your Loved One Stuck in the Past? 4. Treatments That Can Help with PTSD and Other Problems 5. Finding a Therapist II. Helping Yourself, Helping the Survivor 6. Taking Care of Yourself 7. Setting Limits 8. Communicating Your Needs III. Coping with Specific Traumas 9. When Someone You Love Has Been Sexually Assaulted 10. When Someone You Love Has Been to War IV. Putting Your Lives Back Together 11. Reconnecting with Your Partner and Helping Your Children 12. Recovery and Beyond Resources .
Keywords: Post-traumatic stress disorder -- Popular works; Post-traumatic stress disorder